PENGARUH PENGGUNAAN PUPUK ORGANIK KOTORAN SAPI DAN KCL TERHDAP PERTUMBUHAN DAN PRODUKSI TANAMAN BWANG MERAH (Allium Ascalonicum L.) - Sumatera Tarigan; Nani Kitty Sihaloho; Chaula Lutfia Saragih; Donatus Dahang; Radison Sihotang (Universitas Quality, 2022)
Research on the Effect of the Use of Organic Cow Manure and KCL on the Growth and Production of Shallots (Allium Ascalonicum L.) has been carried out in May-August 2021 at UPT. Parent Seeds of Kutagadung Berastagi Horticulture. The aim of the study was to determine the effect of the right combination of cow dung and KCL fertilizer on the growth and production of the Batu ijo variety of shallots. The results showed that the effect of KCL fertilizer on plant height was that K0 (19.97 cm) was significantly different from K1 (22.35 cm), K2 (27.35 cm), and K3 (30.41 cm), and the effect of cow manure O0 (21.97 cm) was significantly different from O2 (25.52 cm) and O3 (27.89 cm) but not significantly different from O1 (23.7 cm). The average leaf growth at 8 WAP with the effect of K level was K0 (26.75 cm), K1 (17.17 cm), K2 (27.08 cm), and K3 (26.75 cm). Meanwhile, the influence of the O factor is O0 (26.33 cm), O1 (27.08 cm), O2 (27.25 cm), and O3 (27.08 cm). Onion crop production per sample had the effect of K0 level (88.7 g), significantly different from K1 (106.2 g), K2 (125.5 g), and K3 (137.1 g) and the effect of cow manure O0 ( 106.9 g) was significantly different from O1 (112.7 g), O2 (115.5 g), and O3 (122.3 g). The number of tubers affected by KCL fertilizer was K0 (8.6) significantly different from K1 (10.2), K2 (14.2), and K3 (15.04), and the effect of cow manure O0 (9) was significantly different from O1 (11,2), O2 (13,6), and O3 (14,2). Onion bulb diameter was significantly different from KCL K0 (1.46 cm) fertilizer with K1 (1.96 cm), K2 (2.66 cm), and K3 (3.24 cm), and the effect of cow manure O0 (2, 01 cm ) was significantly different from O1 (2.21 cm), O2 (2.41 cm), and O3 (2.69 cm). Wet weight of tubers per plot of KCL K0 (1.07 kg) was significantly different from K1 (1.33 kg), K2 (1.83 kg), and K3 (2.18 kg), and the effect of cow manure O0 (1 .04 kg) was significantly different from O1 (1.49 kg), O2 (1.88 kg), and O3 (2 kg).